B27 Abnormal bioenergetics in inclusion-containing mutant HTT exon 1 primary human neurons. (13th September 2016) - Wood-Kaczmar, Alison; Ghosh, Rhia; Kriston-Vizi, Janos; Smith, Edward J; Chadwick, Wayne; Hargreaves, Iain P; Heales, Simon J; Abramov, Andrey Y; Cole, Sarah L; Ketteler, Robin; Bates, Gillian P; Andre, Ralph; et al.
Abstract : Background: Mitochondrial dysfunction is a known component of HD pathogenesis, but the precise mechanisms and temporal order of events linked to mHTT inclusion formation and neurodegeneration are unclear. For example, observations from clinical samples and in vitro models implicate respiratory impairment and enhanced glycolysis in HD cells. Aim: To identify early signs of mitochondrial dysfunction and perturbed bioenergetics in a human HD neuronal model, and better understand the interaction between the proteotoxic environment of mHTT-expressing cells and their metabolic capacity. Methods: We are using a human neural stem cell (NSC) line (ReNcell VM) that over-expresses huntingtin (HTT) exon 1 fragments with either normal (29Q) or pathogenic polyglutamine tracts (71Q and 129Q), and can be rapidly differentiated into mixed populations of neurons and glia in various culture formats. The pathogenic HTT exon 1 lines develop both intranuclear and cytoplasmic mHTT-containing inclusions, as well as accumulating a diffuse aggregated form of mHTT in a time and poly Q-dependent manner. We have correlated with this measures of oxygen consumption rate and extracellular acidification rates using an XF96 Seahorse Bioanalyser, mitochondrial volume and basal ΔΨm by live confocal imaging and potential impairment individual respiratory chain complexes using in vitro assays. Results: Despite no overt reduction in cell viability in the mHTT exon 1 expressing lines we have uncovered sub-pathological alterations to mitochondrial function. We report differences in key respiratory parameters (e.g. basal and maximal respiration) in line with a significant decrease in basal mitochondrial ΔΨm in mHTT exon 1 cells. Here, we will present our findings correlating the inclusion phenotypes and mitochondrial dysfunction in the presence of mHTT exon 1. Conclusions: We have established a robust and disease-relevant in vitro cellular model of HD that has revealed potentially important early changes to neuronal bioenergetics and mitochondrial function. Using this system we aim to not only identify novel pathways in disease pathogenesis that may be amenable to therapeutic targeting, but also to simultaneously develop a novel in vitro cellular platform for high-throughput compound screening.